THE INFLUENCE OF PARENTAL GUIDANCE AND LEARNING MOTIVATION ON STUDENT MATHEMATICS LEARNING OUTCOMES BASED ON STUDENT EMOTIONAL INTELLIGENCE - Sunyoto Hadi Prajitno; Tania Ismi Aulia (IAIN Ambon, 2022)
The emotional intelligence of students is an essential aspect in achieving learning results, particularly in mathematics. This study intends to identify the impact of parental supervision and learning motivation on mathematics learning outcomes at Wahid Hasyim 8 Waru Middle School in terms of high, medium, and low emotional intelligence. This research utilizes quantitative research methods by doing ex-post facto. In collecting data, the researcher uses surveys and documentation. The questionnaire instrument contains three questionnaires, including a parent guidance questionnaire, a learning motivation questionnaire, and an emotional intelligence assessment. While documentation is used to collect statistics on student learning outcomes, it also serves as a means of communication between instructors and students. The results of hypothesis testing from the results of parental guidance and learning motivation on student learning outcomes are reviewed in terms of high emotional intelligence with an F count of 40,661 and an F sig of 0.024, moderate emotional intelligence with an F value of 5.288, and an F count of 0.010, and emotional intelligence with an F value of 7.073 and an F sig of 0.049. The association between mathematical learning results, parental supervision, and learning motivation in terms of emotional intelligence might be described as good and significant.